A novel adiponectin receptor agonist (AdipoAI) ameliorates type 2 diabetes‐associated periodontitis by enhancing autophagy in osteoclasts. (4th January 2022) - Wu, Xingwen; Sun, Yang; Cui, Renjie; Qiu, Wei; Zhang, Jin; Hu, Zhekai; Bi, Wei; Yang, Fei; Ma, Duan; Van Dyke, Thomas; Tu, Qisheng; Yu, Youcheng; et al.
Abstract: Background and Objective: Type 2 diabetes (T2D)‐associated periodontitis is severe and refractory in many cases. Considered an inflammatory disease, T2D predisposes to periodontitis by increasing whole‐body inflammation. One mechanism of increased inflammation is thatT2D is mediated by loss of production or function of the anti‐inflammatory hormone adiponectin. In our previous report, AdipoRon, an adiponectin receptor agonist, and AdipoAI, a newly discovered, more specific agonist, attenuated T2D‐associated inflammation by inhibiting osteoclastogenesis and LPS‐induced endotoxemia. Autophagy plays an important role during osteoclast differentiation and function. The impact of AdipoAI on osteoclast function and autophagy involved in osteoclastogenesis is not known. Here, we compare AdipoRon and AdipoAI potency, side effects and mechanism of action in T2D‐associated periodontitis. Methods: The RAW 264.7 cell line was used for in vitro studies. We analyzed the potential cytotoxicity of AdipoAI using the CCK‐8 assay. The anti‐osteoclastogenic potential of AdipoAI was studied by real‐time qPCR and tartrate‐resistant acid phosphatase staining. The actions of AdipoAI involved in autophagy were tested by real‐time qPCR, western blot and immunofluorescence staining. In the diet‐induced obesity model of T2D, we investigated the impact of AdipoAI on fasting blood glucose, alveolar bone loss, and gingival inflammation in mice with experimental periodontitis. Results: AdipoRon inhibited osteoclastogenesis and AdipoAI inhibited osteoclastogenesis at lower doses than AdipoRon without any cytotoxicity. In DIO mice with experimental periodontitis, AdipoAI reduced mouse body weight in 14 days, reducing fasting glucose levels, alveolar bone destruction, osteoclast number along the alveolar bone surface, and decreased the expression of pro‐inflammatory factors in periodontal tissues. AdipoAI and AdipoRon also enhanced LC3A/B expression when cultured with RANKL.3‑Methyladenine, a known autophagy inhibitor, decreased LC3A/B expression and reversed the inhibition of osteoclastogenesis during AdipoAI treatment. Conclusions: Our results demonstrate that AdipoAI ameliorates the severity of T2D‐associated periodontitis by enhancing autophagy in osteoclasts at lower doses than AdipoRon without demonstrable side effects. Thus, AdipoAI has pharmaceutical potential for treating diabetes‐associated periodontal disease.